A schematic for comparing web backend application frameworks - With regards to performance and scalability - Dosé, Mathias; Lilja, Hampus (My University, 2015)
This thesis aim to engineer a schematic that is to be used for evaluating and comparing web backend application frameworks with regard to responsiveness and load scalability. A partial study was conducted in order to determine what affects these characteristics of performance in a web backend application framework. These findings were named and defined as influences, which where mapped to microbenchmarks called test types. These test types in combination with methods to visualize the results constitute the schematic. The schematic was evaluated through a running example where Express.js and .NET MVC was compared. The schematic proved successful as it was possible to draw a conclusion about these frameworks from the results in the context of use.
Keywords: Informations- och kommunikationsteknik; Data- och informationsvetenskap; Information & Communication Technology; Computer and Information Science